Postmodern archival science and contemporary diplomatics New approaches for archival knowledge organization - Tognoli, Natália Bolfarini [UNESP]; Chaves Guimaraes, Jose Augusto [UNESP] (Ergon-verlag Gmbh, 2010)
New information technologies and new forms of documentary production have led archivists to rethink the role of archival science in the so-called information age. Since the late 1980s, the principles, methods and concepts stated by the well-known manuals of the 19th and the 20th centuries have been reconsidered along with their application to the organic sets of document in the 21st century. In this new scenario of reformulation and reinterpretation regarding the perspectives on archival knowledge organization, two trends with different approaches have emerged in North America and Europe: postmodern archival science and contemporary diplomatics, respectively. The first one was introduced by Terry Cook, who proposed a reformulation of the basic concepts and the functional analysis method focusing on the process and context of document creation. The second approach originated in Italy and incorporated all the theoretical and methodological models of classic diplomatics. The studies following this new trend were disseminated by Luciana Duranti and aimed to ensure the production, access and use of the documentation generated in the present times focusing on document typology, as opposed by the postmodern approach. The purpose of this study is to elucidate the connection points and distinct features between the two trends concerning the organization of archival knowledge.